MANAJEMEN SARANA DAN PRASARANA DALAM MENUNJANG PROSES PEMBELAJARAN DI DAYAH TAUTHIATUTH THULLAB ARONGAN PUTRI - Edimizwar; Rahmah, Mawaddatur (LPPM IAI Almuslim Aceh, 2023)
The problem of this research is how are the obstacles and management solutions for facilities and infrastructure in supporting the learning process at the Tauthiatuth Thullab Arongan Putri Islamic boarding school. This study aims to determine the management of facilities and infrastructure in supporting the learning process at the Tauthiatuth Thullab Arongan Putri Islamic boarding school and to find out the obstacles and solutions for the management of facilities and infrastructure in supporting the learning process at the Tauthiatuth Thullab Arongan Putri Islamic boarding school. This study uses a field research approach (Field Research), namely data collection is carried out in the field. The nature of this research is descriptive qualitative research. In the data collection process, researchers used observation, interview, and documentation methods found at the Tauthiatuth Thullab Arongan Putri Islamic boarding school. In analyzing the data, the researcher used the data analysis technique of the Miles and Huberman models which included data reduction, display data, conclusion drawing/verification data. The research findings inform: That the obstacles to management of facilities and infrastructure at the Tauthiatuth Thullab Arongan Putrin dayah are lack of funds, lack of human resource capabilities, and limited facilities and infrastructure in supporting the learning process. And the solutions for management of facilities and infrastructure at the Tauthiatuth Thullab Arongan Putrin Islamic boarding school are: (1) analyzing the needs of the Islamic boarding school by having a lot of deliberations with the teachers in the Islamic boarding school so that future HR capabilities are given more attention and these facilities and infrastructure are useful and beneficial for the Islamic boarding school in supporting the learning process. (2) identify the needs of the dayah either through direct control or through input and reports received from staff, teachers and students.